Internal Audit versus External Audit: A Qualitative Perspective - Pramukti, Andika (Manunggal Halim Jaya, 2024)
This qualitative study examines the roles, methodologies, effectiveness, and challenges of internal audit versus external audit within organizational contexts. The research aims to provide insights into the distinct yet complementary functions of internal and external audit, shedding light on their contributions to organizational governance, risk management, and financial reporting integrity. The study employs a comprehensive literature review approach, synthesizing existing research to explore definitions, conceptual frameworks, methodologies, practices, and assessments of effectiveness in both audit functions. Key findings reveal that internal audit serves as a proactive advisor to management, focusing on enhancing operational efficiency, strengthening internal controls, and driving continuous improvement and innovation. Conversely, external audit acts as a safeguard for external stakeholders, providing assurance on the reliability and integrity of financial statements. Methodologies and practices vary between internal and external audit, with internal audit employing risk-based auditing, compliance auditing, and performance auditing approaches, while external audit adheres to auditing standards and regulations. Despite their distinct roles, both audit functions face challenges related to audit quality, independence, and relevance. The study underscores the importance of understanding and leveraging the multifaceted contributions of internal and external audit to navigate the complexities of the modern business environment effectively.